A Research on Factors Impacting Occupational Satisfaction of College Teachers: A Case Study of Dezhou University of Technology in China - Xu, Shanshan (Scholar: Human Sciences, 2026)
Purpose: The study investigates the influence of five independent variables (Teacher’s Self-efficacy, Teacher’s Career Motivation, School Climate, Principal’s Transformational Leadership, and Principal’s Transactional Leadership) on one dependent variable (Teacher’s job satisfaction). Additionally, it aims to identify significant differences between variables. Research design, data, and methodology: The research employed the Index of Item-Objective Congruence (IOC) for validity and a Cronbach’s Alpha in a pilot test (n=40) for reliability. 280 valid responses from lectures at a college were analyzed by multiple linear regression to verify the significant relationship between variables. Following this, 40 lectures underwent a 14-week Intervention Design Implementation (IDI). Afterward, the quantitative results from post-IDI and pre-IDI were analyzed in the paired-sample t-test for comparison. Results: In multiple linear regression, the study revealed that teacher’s self-efficacy, teacher’s career motivation, school climate, principal’s transformational leadership, and principal’s transactional leadership had a significant impact on teacher’s jobs satisfaction. Finally, the results from the paired-sample t-test for comparison demonstrated a significant difference in teacher’s self-efficacy, teacher career motivation, school climate, principal’s transformational leadership, and principal’s transactional leadership between the post-IDI and pre-IDI stages. Conclusions: This study aims to explore the factors that affect the professional satisfaction of college lectures to improve the teaching quality of colleges and universities.